2022
DOI: 10.1021/acsaom.2c00071
|View full text |Cite
|
Sign up to set email alerts
|

Hematene Nanoflakes: A Non-van der Waals Material with Superior Nonlinear Optical Properties

Abstract: Stable and efficient optical limiters for eye and sensor protection have been in great demand ever since the advent of high-power lasers. In this study, we report the preparation of highly stable hematene nanoflakes for optical limiting applications by a facile exfoliation method from a low-cost, non-van der Waals material. Optical and structural characterization has been carried out to confirm the structure, morphology, and composition of the hematene nanoflakes. Open aperture Z-scan measurements have been ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…( 1), the average values of the nonlinear absorption coefficient β of hematene and magnetene were determined to be (58.9 � 5.0)×10 À 11 determined β value of hematene, under 532 nm laser excitation, is in very good agreement with the corresponding value obtained in ref. [30], which was reported to be 13×10 À 11 m/W. It is worth noting that similar Z-scan measurements performed under 4 ns, 1064 nm laser excitation, revealed negligible NLO absorption for all samples studied (see Figure S1).…”
Section: A Nlo Responsesupporting
confidence: 59%
See 2 more Smart Citations
“…( 1), the average values of the nonlinear absorption coefficient β of hematene and magnetene were determined to be (58.9 � 5.0)×10 À 11 determined β value of hematene, under 532 nm laser excitation, is in very good agreement with the corresponding value obtained in ref. [30], which was reported to be 13×10 À 11 m/W. It is worth noting that similar Z-scan measurements performed under 4 ns, 1064 nm laser excitation, revealed negligible NLO absorption for all samples studied (see Figure S1).…”
Section: A Nlo Responsesupporting
confidence: 59%
“…[21] Initial application-oriented research efforts has revealed that non-vdW 2D materials are promising candidates for electrocatalysis, [22,23] energy storage, [24] and magnetophotoconductivity. [25] In addition, since non-vdW 2D materials display high carrier mobility, [26] tunable energy bandgap through facile surface modification due to the abundance of dangling bonds, [27] and superior nonlinear optical (NLO) response than their van der Waals 2D counterparts, [28][29][30] it is speculated that they could find numerous applications in photonics and optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, A–D–A type compounds 1–5 show a more excellent NLO property with higher β eff and Imχ (3) values than some reported materials (Table S11). , Thus, these compounds can be considered as promising OL materials in laser protection.…”
Section: Resultsmentioning
confidence: 99%
“…So far, several methods such as Z-scan, four wave mixing, multiphoton microscopy, and spatial self-phase modulation (SSPM) techniques have been utilized to probe the third-order NLO refraction coefficient ( n 2e ) in numerous 2D materials. , However, Z-scan and four-wave mixing techniques require comparatively complicated experimental arrangements and data interpretation . Furthermore, due to the use of a high-power laser in the experiments, overcoming the experimental error due to self-diffraction of the laser beam is quite tricky, particularly for Z-scan experiments .…”
Section: Introductionmentioning
confidence: 99%